The poem “Bunga Ilmu Itu” by Dinullah Rayes:Riffaterre's Semiotic Studies - Diana, Jumianti; Patihah, Marwah Ernia (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to reveal the meaning of the poetry and text which became the background for the creation of the poem